Mesa redonda após o seminário "Juventude e trabalho" - Feffermann (Palestrante), Marisa; Fernandes (Palestrante), Angela Viana Machado; Caccia-Bava (Mediador), Augusto (Revista Segurança Urbana e Juventude, 2009)
Researchers, educators and students debate demanded questions and possible reflections about the daily difficulties of young people seriously and accurately. The searching for explanations, the speaking about regarding on their experiences and changing´s desire are some of the high points of these meeting.